2019
DOI: 10.3390/cancers11111730
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of CD8+ T Lymphocytes in Childhood Adrenocortical Carcinomas Compared to Ki-67, PD-1, PD-L1, and the Weiss Score

Abstract: Adrenocortical carcinoma (ACC) is a rare disease among children. Our goal was to identify prognostic biomarkers in 48 primary ACCs from children (2.83 ± 2.3 y; mean age ± SD) by evaluating the tumor stage and outcome for an age of diagnosis before or after 3 years, and association with ACC cluster of differentiation 8 positive (CD8+) cytotoxic T lymphocytes (CD8+-CTL) and Ki-67 immunohistochemical expression (IHC). Programmed death 1(PD-1)/Programmed death-ligand 1 (PD-L1) immunohistochemistry (IHC) in ACC was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 66 publications
0
39
1
1
Order By: Relevance
“…Thirty‐six papers 2,5,16–18,20–47,49,50 allowed the evaluation of gender effect on outcome: females were found to have RR of 1.21, without reaching a significance ( P = .14; 95% CI 0.94‐1.55; I 2 0%).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐six papers 2,5,16–18,20–47,49,50 allowed the evaluation of gender effect on outcome: females were found to have RR of 1.21, without reaching a significance ( P = .14; 95% CI 0.94‐1.55; I 2 0%).…”
Section: Resultsmentioning
confidence: 99%
“…CD4 + T cells are helper T cells, stimulating CTLs activities (37). In addition, ACCs were also relatively frequently detected in childhood and increased TILs were reported in those young ACCs patients than adults (49). The most notable difference between ACCs and PHEOs was considered the effects of different hormones on TILs.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies showed that the immune response may have an important role in influencing the clinical course of patients with ACC. In pediatric ACC, MHC class II expression by tumor-infiltrating hematopoietic cells and the number of CD8 + T-lymphocytes are important prognostic indicators [13,20]. Even if in general only a small percentage of ACC tumor cells express PDL1, as detected by IHC [17,18], higher levels of PDL1 mRNA expression are significantly correlated with an inflammatory gene expression signature and longer DFS of adult patients with ACC [21].…”
Section: Discussionmentioning
confidence: 99%